Increased osteoclastogenesis in patients with vertebral fractures following discontinuation of denosumab treatment. Issue 6 (June 2017) - Anastasilakis, Athanasios D; Yavropoulou, Maria P; Makras, Polyzois; Sakellariou, Grigorios T; Papadopoulou, Fotini; Gerou, Spyridon; Papapoulos, Socrates E
Abstract : Objective: To test the hypothesis that rebound of bone remodeling is responsible for clinical vertebral fractures reported in a few patients with osteoporosis after cessation of denosumab treatment. Design: In this case-control study we compared clinical and biochemical characteristics of postmenopausal women with clinical vertebral fractures 8–16 months after the last injection of denosumab (Dmab/Fx+, n  = 5) with those of treatment-naïve women with such fractures (Fx+, n  = 5). In addition, 5 women who discontinued denosumab treatment but did not sustain vertebral fractures 18–20 months after the last injection were studied (Dmab/Fx−, n  = 5). Methods: We measured serum microRNAs, gene expression of mRNAs of factors regulating formation and activity of osteoclasts and biochemical markers of bone and mineral metabolism. In Dmab/Fx+ and Fx+ women, blood was taken 4–8 weeks after the fracture. Results: Compared to Fx+ women, Dmab/Fx+ women had higher serum P1NP and CTx levels, and significantly lower serum miR-503 and miR-222-2 that downregulate osteoclastogenesis and osteoclast activity, and higher RANK (13-fold) and CTSK (2.6-fold) mRNA. The respective values of Dmab/Fx− women were in the same direction as those of Dmab/Fx+ women but of a lesser magnitude. Conclusions: Bone fragility in women with clinical vertebral fractures after stopping denosumab therapy is pathophysiologically different from that of treatment-naïve women with osteoporosis and clinical vertebral fractures and it is associated with upregulation of markers of osteoclast formation and activity. The small number of women with this rare event studied is a limitation.